Pengaruh Harga, Lokasi, Promosi, Dan Kualitas Pelayanan Terhadap Minat Beli Konsumen Pada Alfamart 12B Trimurjo Kabupaten Lampung Tengah - Fuadi, Selamet; Dipa, Nely Trisna; Shar, Aan (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze the effect of price, location, promotion, and service quality on consumer buying interest at Alfamart 12b Trimurjo, Central Lampung Regency. This type of research is a quantitative research with a population of 100 consumers. Only 100 samples used were in accordance with the predetermined criteria. The data used is secondary data distribution of questionnaires in the form of a list of questions with several alternative answers for respondents. The statistical test used to test the hypothesis was multiple linear regression analysis and was tested using the statistical packages for the social science (SPSS) version 25 program. Based on the results of statistical tests indicate that price has a positive influence on consumer buying interest, location has a positive influence on consumer buying interest, promotions have a positive influence on consumer buying interest, service quality has a positive influence on consumer buying interest.